First report of fungal disease in a South American snake - Bustos, María Lucía (2018)
The Snake Fungal Disease (SFD) has been reported in several species of rattlesnakes and colubrid snakes in the United States of America and Europe, but not in South America. A specimen of the South American colubrid (Xenodon merremii, commonly known as false yarara) was presented at the Servicio de Emergencias del Hospital de Clínicas de la Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste (Argentina), presenting a crusty open wound in the skin, and another injury consisting of discolored and dull scales. The specimen died 16 days after starting the treatment. At necropsy, lesions in the hepatic parenchyma were observed, whereas the lung showed no appreciable macroscopic lesions. The lesions found in this case were compatible with SFD.